Psychological Well Being Youth Inventory for Domestic Violance Victims : Rasch Model Analysis - Fadli, Rima Pratiwi; Alizamar, Alizamar; Afdal, Afdal; Ifdil, Ifdil (COUNS-EDU: The International Journal of Counseling and Education, 2019)
Domestic violence is a long-standing phenomenon in society. Domestic violence impacts the physical and psychological, especially related to the psychological wellbeing of the victims who experience, witness and observe the domestic violence. The victims included children from parents who experienced domestic violence, namely children and adolescents. Based on this, the researcher designed a research instrument to identify the conditions of the psychological well-being of adolescents living with parents who experienced domestic violence. This instrument was tested with 30 respondents from the vocational high school Y students in Padang City. The results of the trial were analyzed using rasch models. The test results describe that this instrument is feasible to use. It is seen from the construct of this instrument to meet the requirements of things that must be measured, the results of the validity of the items there are 8 items considered not to be used. The reliability value of this instrument item is 0.89 and the reliability of the person is 0.91. These results show that this instrument is feasible to be used to measure the psychological well condition of being a teenager living with a domestic violence parent.